2009
DOI: 10.1021/ja907055q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cell-Active Lysine Specific Demethylase 1-Selective Inhibitors

Abstract: Lysine specific demethylase 1 (LSD1) plays a key role in the regulation of gene expression by removing the methyl groups from methylated Lys4 of histone H3 (H3K4). Here we report the identification of the first small-molecule LSD1-selective inhibitors. These inhibitors show in vivo H3K4-methylating activity and antiproliferative activity and should be useful as lead structures for anticancer drugs and as tools for studying the biological roles of LSD1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 12 publications
3
171
0
Order By: Relevance
“…3e). To determine whether the demethylase activity of Lsd1 accounts for the observed migration phenotype, we additionally performed migration analysis of wild-type TSC in the presence of specific Lsd1 inhibitors 31,32 . Similar to the deletion of Lsd1, inhibitor treatment causes a significant increase in TSC migration indicating that the enzymatic activity of Lsd1 is essential ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3e). To determine whether the demethylase activity of Lsd1 accounts for the observed migration phenotype, we additionally performed migration analysis of wild-type TSC in the presence of specific Lsd1 inhibitors 31,32 . Similar to the deletion of Lsd1, inhibitor treatment causes a significant increase in TSC migration indicating that the enzymatic activity of Lsd1 is essential ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell migration and invasion were monitored using the xCelligence system (Roche). 1-(4-methylpiperazin-1-yl) ethan-1-one) 32 , substance 2 (trans-N-[1-(2,3-dihydro-1,4-benzodioxin-6-yl)ethyl]-2-phenylcyclopropan-1-amine) 31 , substance 3 (trans-N-[(2-methoxypyridin-3-yl) methyl]-2-phenylcyclopropan-1-amine) 31 or DMSO. Cell indices were automatically recorded every 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…LSD1 knockout mice die early in development (15), and LSD1-null embryonic stem cells showed impaired viability (16), suggesting that LSD1 plays a crucial role in cell functions. Several studies showed that overexpression of LSD1 drives cell proliferation in various cancers (17)(18)(19)(20). We have recently found that LSD1 suppresses mitochondrial respiration and maintains energy storage in murine adipocytes under the obese condition (21).…”
Section: Introductionmentioning
confidence: 97%
“…40,277 Recently, based on the crystal structures of FAD-PCPA adduct and the FAD-N-propargyl lysine peptide adduct complex with LSD1 279,280 , Ueda and coworkers designed a series of PCPA-lysine hybrid compounds and evaluated their inhibitory activities targeting at LSD1 and MAO-A and MAO-B. 281 Among the four synthesized compounds, the LSD1 inhibitory activities of compound 1 and 2 ( Figure 17) were over 10-fold more potent than that of PCPA (IC 50 values: PCPA = 32 μM; 1 = 2.5 μM; 2 = 1.9 μM). In particular, compound 1 and 2 specifically inhibit LSD1 in comparison to MAO-A and -B (the IC 50 values against MAO-A are 230μM and 500μM; The IC 50 against MAO-B: 290μM and >1mM).…”
Section: E Inhibitors Of Histone Lysine Demethylasesmentioning
confidence: 99%